Comparison of the effects of 8 weeks of high intensity interval training and continuous training on P-selectin expression and platelet indices in cardiovascular disease - سجاد احمدی زاد; مجید ملکی; نسیم نادری; هیوا رحمانی; اکبر نوری حبشی; مرتضی سلیمیان; سارا لطفیان (Shahid Beheshti University, 2016)
Platelets play an important role in the etiology of cardiovascular disease. The aim of this study was tocompare the effects of 8 weeks of high intensity interval training and continuous training on P-selectinexpression and platelet indices in cardiovascular patients. Therefore, 30 CABG and PCI heart patientvoluntary participated and divided into three groups (n=10): control, continuous and high-intensity intervalgroup. Anthropometric characteristics and peak oxygen consumption was recorded before starting a workout.Each session was 40 minutes. Interval session consists of warm-up, 8 reps/ four min (exercise: 2min, activerecovery: 2min, intensity: 90 /30) and cool down, but continues session includes 30 minutes of continuousexercise intensity activity with 60% of peak oxygen consumption. The control group did not have a regularactivity. Blood samples taken before and after the eight-week and their P-selectin (by flow cytometry) andplatelet indices were measured. Repeated measure ANOVA with between group factor and multiple linearregression were used for statistical analysis. The results showed that P-selectin expression changes betweenthe groups were significantly different (P=.013). Post-hoc test show that the changes between control andinterval groups were significant (P=.011). But no significant changes were observed in all platelet indices(P>0.05).It is concluded that eight weeks of exercise leads to reduction in P-selectin expression that was alsoaffected by type of activity. Based on more effects of interval training in cardiovascular patients, use ofinterval training can be suggested in their rehabilitation program.